Perceived academic concerns of under graduate medical students: a study of student’s perspective - ., Priyanka; Goel, Manish Kumar; Rasania, Sanjeev Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: With the drastic increase in the number of under graduate medical seats in India, the quality of medical education is facing challenges. To address these issues, curricular reforms have been advocated. Medical students are one of the stakeholders and their perceptions regarding medical education system hold a lot of importance. Methods: This study was conducted by the department of community medicine of a premier medical institute of Delhi and involved analysis of 457 feedback forms filled by medical students about their academic concerns and their perceptions about ways to address these concerns. The responses were kept anonymous. They were read several times and were grouped to deduce meaningful information in order to reach an overall understanding. Results: The medical students were concerned about the lengthy curriculum, long duration of lectures, language barrier and inappropriate assessment methods used. Lack of proper time management and recreational facilities were also pointed out. To address these concerns, they suggested some modifications in teaching and assessment methods like shorter and more interactive lectures, more focus on small group interactive teaching, healthier and friendlier teacher-student relationship and less frequent and skill-based assessment. Conclusions: The concerns and suggestions made by students are important and valid. Most of these issues have already been taken up in latest modifications in medical education by Medical Council of India. The competency based medical education program which has been implemented recently has called for major reforms, which are also the felt needs of medical students.